Penentuan Rute Optimal pada Pengangkutan Sampah di Kota Palembang dengan Menggunakan Metode Saving Matrix - Indrawati Indrawati; Ning Eliyati; Agus Lukowi (Faculty of Mathtmatics and Natural Sciences, 2016)
: Determination of the optimal route on garbage transportation from several TPS (Temporary Landfill Dump) to TPA (End Landfill Dump) is a form of VRP (Vehicle Routing Problem). One of the method in VRP to minimize the mileage and maximize the volume of garbage transported in accordance with the capacity of the vehicle is saving matrix method . There were four amroll vehicles that operating to transport garbage at 11 TPS’s in Kecamatan Ilir Timur I Kota Palembang. Each amroll has a working area , assuming the volume of garbage at each TPS remained . Based on the data obtained in DKK (Dinas Kebersihan dan Keindahan), there is only 1 Amroll that transporting the volume of garbage in accordance with the amroll capacity (5 m3 ) . The obtained optimal route can save mileage of 181.8 km or 2.84% . There are 3 amrolls which can carry garbage volume maximally in accordance with maximum capacity of Amroll.